Determination of the fungal community of pit mud in fermentation cellars for Chinese strong-flavor liquor, using DGGE and Illumina MiSeq sequencing. (January 2017) - Liu, Maoke; Tang, Yuming; Zhao, Ke; Liu, Ying; Guo, Xiaojiao; Ren, Daoqun; Yao, Wanchun; Tian, Xinhui; Gu, Yunfu; Yi, Bin; Zhang, Xiaoping
Abstract: Chinese strong-flavor liquor (CSFL) is fermented in cellars lined with pit mud (PM). This PM, specific fermented clay, contains microbes that play important roles in CSFL production. However, there is limited information about fungal community structure and cellar-age-related changes in PM. In this study, PM samples were removed from the cellars used for 5 and 100 years and characterized using denaturing gradient gel electrophoresis (DGGE) and Illumina MiSeq sequencing. Both methods revealed there were no significant differences in fungal species diversity (Shannon index, Chao1, and observed species) between the 5- and 100-year PM samples ( p  > 0.05), but the communities were more stable in the 100-year PM samples (UPGMA). Illumina MiSeq sequencing allowed identification of 111 fungal genera belonging to 4 phyla (Ascomycota, Zygomycota, Basidiomycota, and Chytridiomycota) in the PM samples, with the predominant phylum being Ascomycota. The results also indicated that the compositions of dominant genera in the PM samples were significantly changed during long-term CSFL fermentation. There were relatively more Rhizopus, Phoma, and Trichosporon in the 5-year PM samples, and Aspergillus and Candida were most highly represented in the 100-year PM samples ( p  < 0.05). Of these, Candida increased its relative abundance significantly in the 100-year samples ( p  < 0.05). Overall, the results provide novel insights into the fungal community associated with CSFL production, and may suggest why fermentation in a cellar with PM that has been in usage for a longer time allows better quality CSFL production. Graphical abstract: Highlights: Fungal community in pit mud of Chinese liquor is revealed by DGGE and NGS. A total of 111 genera belonging to 4 phyla are found. Nineteen core genera that play key roles in liquor production are identified. Fungal succession in pit mud may contribute to the improvement of liquor quality.